Voluntary agreements and competition law - Hans H. B. Vedder (Fondazione Eni Enrico Mattei (FEEM), 2000)
Many voluntary agreements (VA's) fall under the European or Dutch cartel prohibition (Article 81 EC, Article 6 Mededingingswet). This paper starts with an abstract description of the relation between competition and environmental protection. Particular attention is paid to the role in this relation of the "integration" and "polluter pays" principles enshrined in, respectively, Article 6 and 175 EC. After that it describes current European and Dutch competition policy vis a vis VA's. The paper concludes with some recommendations of what competition policy as regards VA's should be. These recommendations are primarily based on legal reasoning.
Keywords: L41; L42; L44; 330; Environmental agreements; competition law; Dutch competition law; European competition law; integration principle; polluter pay principle; voluntary agreements; Selbstverpflichtung; Kartellrecht; Konzentrationspolitik; Niederlande; EU-Staaten